Sexual behaviour and copulation of castrated males on the induction of ovulation in alpacas - Urviola S., Jesús (2022)
The aim of this study was to evaluate the effect of the sexual behaviour process of copulation with castrated males (G1) on ovulation induction, contrasting with the same effect of vasectomized males (G2) and the effect of the application of seminal plasma (G3) in utero in 45 alpacas with preovulatory follicle ≥7 mm in diameter, randomly distributed (n=15) in each experimental group. The occurrence of ovulation was estimated on day 4 post-copula by sexual receptivity (acceptance or rejection) to the male and verified on days 7 and 11 with the detection of a corpus luteum (CL) by transrectal ultrasound. In G1, seminal plasma secretion was determined on days -1, 1, 17 and 21 after castration. The phases of sexual behaviour in the controlled mating were similar between G1 and G2. On day 4 post mating a female from G1 had ovulated. On day 7, the ovulation rate determined by the presence of the CL and sexual receptivity was higher (p<0.05) in G2 (93.3%) than in G1 (26.7%) and G3 (20%). On day 11, all the females were receptive to the male again, with CLs in a regression stage. Seminal plasma volume in G1 decreased (p<0.01) from 1.2 to 0.4 ml. The study shows that castrated males, evaluated 21 days after castration, exhibit the phases of sexual behaviour: courtship, mounting, erection with semi-circular movement of the penis, penetration and copulation, with minimal secretion (0.4 ml) of seminal plasma, but without ejaculate of semen, inducing ovulation in 27% of females.